Makna Lagu Buku Ende No. 17 "Raja Natumimbul" Di GKLI Amborgang Resort Parlilitan Kabupaten Humbang Hasundutan - Amri Tumanggor; Monang Asi Sianturi; Tezti Bazarni Zebua; Eben Haezarni Telaumbanua; Rowilson Nadeak (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study focuses on the study to find out the meaning of the Ende Book Song No. 17 "Raja Natumimbul" and the way the congregation sings the Ende Book song at GKLI Amborgang Resort Parlilitan. This research uses a qualitative method with a research procedure that produces descriptive data in the form of written or spoken words from people and observable behaviors and data collection techniques through the results of interviews, observations, and documentation, The location of the research was conducted at the GKLI Amborgang Ressort Parliltan Church, Sihashabinsaran Village, Parlilitan District, Humbang Hasundutan The object of the research was 6 people, namely to Pastors, Church Teachers, Musicians and to. Thus, it can be concluded that the meaning of the song King Natumimbul has a very deep meaning, which means that here there is a confession of the Lord God, the creator of all things, so that all that he creates praises God because he is the most exalted king of all. The song of King Natumimbul when sung is also full of enthusiasm because this song means that only God is the supreme King, only He is the king who should be worshipped. The hope is that the people of the GKLI Amborgang congregation will receive blessings from God and invite sinners to worship him.